Vitiligo Associated with Melanoma in a Malagasy Woman - I. M. Ranaivo; F. A. Sendrasoa; M. Andrianarison; M. Razakanaivo; L. S. Ramarozatovo; F. Rafaramino; F. Rapelanoro Rabenja (Hindawi Limited, 2019)
Malignant melanoma is the first fatal skin cancer. Vitiligo is a leukoderma or a multifactorial depigmentation acquired but especially of autoimmune origin. We report the first Malagasy case affected by both melanoma and Vitiligo. The appearance of Vitiligo during a melanoma could testify to an immunological response against melanocytes. Despite the association of melanoma and Vitiligo, the prognosis of melanoma is still fatal.